The Notary Responsibility for the Development of Dedies that Contains False Data in the Agreement - Cindy Daniela Lamandasa; Tri Hayati (Budapest International Research and Critics University, 2022)
Notary deed as authentic becomes the strongest and most complete evidence, and has an important role in every legal relationship in people's lives. Therefore, the existence of a notary deed is expected to provide legal certainty and legal protection for the community. However, in practice, it was later discovered that the deed made by a notary contained false data provided by the parties in the deed. Thus, the purpose of writing this scientific article is to analyze how the notary's responsibility is in making a deed with false data and the legal consequences of a deed containing false data. This research is classified as a normative research type supported by secondary data whose data collection is carried out by the library research method and the data obtained from the research results are processed by qualitative methods. The results of this study indicate that if the Notary has fulfilled all the provisions in making a Notary deed correctly, then the Notary deed made based on false data, the Notary cannot be held legally responsible. However, Notaries still need to be careful and uphold the code of ethics of the Notary profession in carrying out their duties and positions. Furthermore, the deed made by a Notary containing falsified data due to the party's error resulted in the deed being null and void.